Associations between specific and cumulative adverse childhood experiences, childhood obesity, and obesogenic behaviours - Ladan Hashemi; Maryam Ghasemi; Brooklyn Mellar; Pauline Gulliver; Barry Milne; Fiona Langridge; Tracey McIntosh; Christa Fouche; Boyd Swinburn (European Journal of Psychotraumatology)
Background: Individuals impacted by adverse childhood experiences (ACEs) are at greater risk of developing obesity, however, few studies have prospectively measured ACEs and obesity during childhood. Associations with the adoption of obesogenic behaviours during childhood, which directly contribute to obesity are also understudied.Objective: To examine associations between individual and cumulative ACEs, obesity, and obesogenic behaviours during childhood.Methods: Data came from Growing Up in New Zealand. The study sample was restricted to those who provided obesity data at age 8 and one child per mother, resulting in an analytic sample of 4895 children. A newly developed ACEs index consisted of nine individual ACEs and cumulative ACEs scores (0, 1, 2, 3, 4+ ACEs), two obesity measures (BMI and waist circumference/height ratio), and eight obesogenic behaviours including unhealthy dietary behaviours, inadequate sleep duration, excessive screen time, and physical inactivity were included in the analyses.Results: ACEs were prevalent among this cohort of NZ children. By age eight, 87.1% of children experienced at least one ACE and 16% experienced at least 4 ACEs. Six individuals assessed ACEs showed significant associations with childhood obesity (AORs ranging from 1.22 to 1.44). A significant dose–response effect was observed where the experience of a higher number of ACEs was associated with greater risk for obesity (AORs increased from 1.78 for one ACE to 2.84 for 4+ ACEs). Further, a significant dose–response relationship was found between experiencing two or more ACEs and higher odds of adopting obesogenic behaviours (AORs ranging from 1.29 for physical inactivity to 3.16 for no regular breakfast consumption).Conclusions: ACEs exposure contributes to population-level burden of childhood obesity. Our findings highlight the importance of a holistic understanding of the determinants of obesity, reinforcing calls for ACEs prevention and necessitating incorporation of ACEs-informed services into obesity reduction initiatives.